Recursos didácticos y tecnológicos para el desarrollo sensorial - Llumigusin Ubillus, Aracely Rosario (2022)
The present project is aimed at solving the problem of insufficient sensory development in children of initial education, against this it has been proposed to design workshops on didactic resources for sensory development in children of Initial Education of the Educational Unit Fourteen of July "JAE" educational period 2022-2023. Qualitative research was used with the inductive method that proposes to evaluate and interpret the information obtained through records and the narrative design was also used, which helped to collect data. Therefore, constructivist-type activities are presented where much more feasible didactic resources are used for student learning and they are able to build their own knowledge since it is the result of previous experiences obtained in the environment. Thus, the workshops are based on educational and technological resources for sensory development in children in which it is intended to develop creativity and imagination, which allows a visual stimulus and thus understand the reaction and triggers in a network ofinter connection to help improve the challenges of logical thinking, new work resources are presented, improving their process of receiving knowledge, but given the change to face-to-face learning. The proposal was validated by experts and three users who have experience with the proposed workshops, assigning a very good rating.